Kandungan nitrogen saat pasang dan surut di Sungai Mahakam Kota Samarinda: Nitrogen content during high and low tides in the Mahakam River, Samarinda City - Kania Karnelia; Ghitarina; Irma Suryana (Fakultas Perikanan dan Ilmu Kelautan, Universitas Mulawarman, 2023)
This study aims to determine the levels of nitrogen compounds in the Mahakam river at high and low tide, and to compare it with the quality standard East Kalimantan Timur Regulation Number 02 0f 2011 concerning Water Quality Management and Water Pollution Control. The data obtained in the field and the results of the analysis in the laboratory are displayed in the form of tables and graphs. The data is presented based on a descriptive picture to get conclusions from the results of the study, with an independent sample t-test and compared the average between the two cases. The levels of Ammonia, Nitrite and Nitrate at high tide were significantly lower than at low tide. lower than at low tide. Ammonia levels at high tide ranged from 0.382- 0.424 mg/L, and have exceeded the quality standard threshold of regional Regulation of East Kalimantan Province Number 02 of 2011. Nitrite levels at high tide range from 0.027- 0.068 mg/L and ar low tide 0.04 - 0.068 mg/L, and still meet the quality standards of East Kalimantan Province Regulation Number 02 0f 2011.Nitrate levels at high tide range from 0.89 – 1.20 mg/L and at low tide 1.00 – 1.20 mg/L, which still meets the quality standards of East Kalimantan Province Regualation No. 01 of 2011. The levels of Ammonia, Nitrite and Nitrate at high and low tide were not significantly different.